Técnicas integrativas de identificação de parasitoides de Bemisia tabaci (Gennadius, 1889) - Moro, Daniela (2021)
The whitefly Bemisia tabaci (Gennadius, 1889) (Hemiptera: Aleyrodidae) is a sucker that causes problems in countless crops of agricultural importance due to its voracity and short life cycle. In general, the control of this pest is carried out with chemical insecticides because they have certain limitations (e.g., period of grace and selection of resistant populations), biological control with the use of parasitoids (mostly of the order Hymenoptera) is currently an important management strategy. Parasitoid wasps of the family Aphelinidae (Hymenoptera) carry out this control by means of both reproduction and feeding processes. Identifying native parasitoid species within agricultural systems affected by whitefly species is the first step in the development of guidelines for the creation and release of biological control agents aimed at this highly harmful pest species complex. Taxonomic and phylogenetic analyzes based on morphological and molecular characters, respectively, confirmed the occurrence of Encarsia formosa (Gahan, 1924) whitefly, attacking tomatoes in a greenhouse in Santa Maria, Encarsia porteri (Mercet, 1928) on soybeans, in the field. opened in Santa Maria and Eretmocerus mundus Mercet, 1931 in tomatoes in a greenhouse in São José do Hortêncio, all in the state of Rio Grande do Sul (Southern Brazil). This is En's first account. beautiful, En. porteri and Er. mundus parasitizing B. tabaci in southern Brazil, and the first partial sequence of the mtCOI gene of En. porteri being reported and characterized. The sex ratio of the studied populations points to a female and male prevalence in the Encarsia and Eretmocerus genders, respectively. The combined use of taxonomic and molecular characterization allows the identification of whitefly parasitoids.